Early diagenesis and trace element accumulation in North American Arctic margin sediments. (15th April 2017) - Kuzyk, Zou Zou A.; Gobeil, Charles; Goñi, Miguel A.; Macdonald, Robie W.
Abstract: Concentrations of redox-sensitive elements (S, Mn, Mo, U, Cd, Re) were analyzed in a set of 27 sediment cores collected along the North American Arctic margin (NAAM) from the North Bering Sea to Davis Strait via the Canadian Archipelago. Sedimentary distributions and accumulation rates of the elements were used to evaluate early diagenesis in sediments along this section and to estimate the importance of this margin as a sink for key elements in the polar and global oceans. Distributions of Mn, total S and reduced inorganic S demonstrated that diagenetic conditions and thus sedimentary carbon turnover in the NAAM is organized regionally: undetectable or very thin layers (<0.5 cm) of surface Mn enrichment occurred in the Bering–Chukchi shelves; thin layers (1–5 cm) of surface Mn enrichment occurred in Barrow Canyon and Lancaster Sound; and thick layers (5–20 cm) of surface Mn enrichment occurred in the Beaufort Shelf, Canadian Archipelago, and Davis Strait. Inventories of authigenic S below the Mn-rich layer decreased about fivefold from Bering–Chukchi shelf and Barrow Canyon to Lancaster Sound and more than ten-fold from Bering–Chukchi shelf to Beaufort Shelf, Canadian Archipelago and Davis Strait. The Mn, total S and reduced inorganic S distributions imply strong organic carbon (OC) flux and metabolism in the Bering–Chukchi shelves, lower aerobic OC metabolism in Barrow Canyon and Lancaster Sound, and deep O2 penetration and much lower OC metabolism in the Beaufort Shelf, Canadian Archipelago, and Davis Strait. Accumulation rates of authigenic S, Mo, Cd, Re, and U displayed marked spatial variability along the NAAM reflecting the range in sedimentary redox conditions. Strong relationships between the accumulation rates and vertical carbon flux, estimated from regional primary production values and water depth at the coring sites, indicate that the primary driver in the regional patterns is the supply of labile carbon to the seabed. Thus, high primary production combined with a shallow water column (average 64 m) leads to high rates of authigenic trace element accumulation in sediments from the Bering–Chukchi shelves. High to moderate primary production combined with deep water (average 610 m) leads to moderate rates of authigenic trace element accumulation in sediments from Lancaster Sound. Low to very low primary production combined with moderate water depths (average 380 m) leads to low rates of authigenic trace element accumulation in sediments in the Beaufort Shelf, Davis Strait and Canadian Archipelago. Authigenic Mo accumulation rates show a significant relationship with vascular plant input to the sediments, implying that terrestrial organic matter contributes significantly to metabolism in Arctic margin sediments. Our results suggest that the broad and shallow shelf of the Chukchi Sea, which has high productivity sustained by imported nutrients, contributes disproportionately to global biogeochemical cycles.